Dynamic soil profile determination with the use of a neural network - Kogut, Janusz (Computer Assisted Methods in Engineering and Science, 2007)
This paper describes an application of feedforward neural network to analyse the SASW (Spectral Analysis of Surface Waves) measurements of the soil. The free field dynamic experiment was performed to determine the soil dynamic properties. An inversion process is based on the comparison of experimental and theoretical phase velocity curves. The results of the experiment are pre-processed by a neural network. The dynamic soil profile is compared with the real soil profile based on the geotechnical site prospect.